PENDETEKSIAN MINAT DAN BAKAT MENGGUNAKAN METODE RIASEC - Fiyan Kurnia Hidayat; Sri Ngudi Wahyuni (Indonesian Journal of Business Intelligence (IJUBI), 2019)
The interests are very important to choosing a course and field of work. Good salary, good company is one of goal in our life. One of many way which we can do for choice and mapping it more early is interest detection for detect our school and faculty which suitable with our interest. One of interest detection method use is RIASEC. RIASEC is one method with use probability principles for compute and compare six elements in it. The expensive price for buying a psychology expert is reason for developing this systems. The system can access bay website and which easy way. It will be helping all people for detection their children interest and will can giving best education for them.